The Effect of National Public Debt on Economic Growth in Kenya - Mohamedamin Ahmed Hassan; B. Onkoba Ongeri; David Katuta Ndolo (European Scientific Journal, ESJ, 2023)
Kenya being a lower middle income  country  compliments  tax  revenue  with  government  borrowing  to  finance  its  national  development  plans. In  an  attempt  to  add  to  available  domestic  resources,  successive  governments  have  relied  on  both  domestic  and  external  debt  to  finance  the  country’s  budget. In  light  of  the  growing  concerns  over  Kenya’s  national  public  debt  sustainability and its  potential  effect  on  the  economy,  this  study  aimed  at  analyzing  the  effect  of  national  public  debt  on  economic  growth  in  Kenya.  Specifically,  the  study  sught  to   establish  the  effect  of  domestic  debt  and  external  debt  on  Kenya’s  economic  growth.  Gross  Domestic  Product  was used as the  proxy  for  economic  growth  while  domestic  debt,  external  debt,  inflation  rate,  exchange  rate,  capital  stock  and  labor  force  are  the  explanatory  variables.  The  study  used  time series  data  for  the  period   990  to  20 9.  The  data  was  extracted  from  the  World  development  indicators  and  this data  was  harmonized  with  data  extracted  from  the  data  bases  of  the  Kenya  National  Bureau  of  Statistics.  The  data  was  analyzed  through  the  Ordinary  Least  Square  (OLS)  regression  technique.  The findings  indicated that domestic  debt  had an insignificant  negative  effect on Kenyan  economy  while  external  debt  has  insignificant  positive  effect. The study  concluded  that  internal  debt  has  deleterious  while  external  debt  has positive  effect  on  growth.